The rise and fall of democracy promotion in US foreign policy - Hill, Matthew Alan, author.
1 online resource
Keywords: "The Rise and Fall of Democracy Promotion in US Foreign Policy employs a Transformational Change framework to understand US democracy promotion from 1977 until the present day. American exceptionalism is a framework that has driven the US since the founding days of the republic, charging the US to promote the universal values of liberty and the pursuit of happiness around the world. Providing a frame of continuity for successive administrations, it reinforces the mythology of American exceptionalism in the eyes of the American people and the world. In different eras, different presidential worldviews, along with different international and domestic factors have shaped how each administration has acted in the international arena and yet all have employed this language regardless of the policies pursued. This timely volume maps-out and interrogates through four key indicators the rise and fall of democracy promotion at the conceptualisation, rhetorical and implementation levels. It argues that there were two transformational changes during this period. The first was the expansion of democracy promotion in US foreign policy and confirmed with the election of Jimmy Carter to the White House in 1977. The second was the rejection of liberal ideology and institutions confirmed with Donald Trump's election in 2016. It is nuanced in that it shows how these changes in the acceptance and then rejection of democracy promotion as a foreign policy tool played out. In examining these two administrations, and those in-between, this work also observes that the rise and fall of democracy promotion as an effective foreign policy tool mirrored the relative dominance of the US in the international arena. This book will be of interest to students and scholars of American foreign policy, international relations, and American history"--